Methotrexate as a Suspected Trigger of Macrophage Activation Syndrome in Juvenile Idiopathic Arthritis - Roy, Soumya; Chakrabartty, Subroto (Journal of Nepal Paediatric Society, 2017)
A four year old girl with systemic onset juvenile idiopathic arthritis (SOJIA) developed macrophage activation syndrome (MAS) shortly after starting methotrexate. We observed methotrexate is a likely trigger of MAS in SOJIA. Possibly, there are only two case reports suggesting methotrexate triggered MAS. We reviewed the literature for possible mechanisms.